Kindness in management and organizational studies - Thomason, Michelle (Kindness at work, 2022)
Kindness in Management and Organizational Studies is the first book in a ground-breaking series exploring Kindness at Work. This edited collection offers multiple perspectives in the understanding, interpretation, enactment, and resistance to the concept of kindness in a business context. Through the diverse offerings of each author we gain and reflect on new knowledge, formulate new questions, and find direction for our next steps. The collection of texts range in topics that include Indigenous storytelling about sanctified kindness to an examination of key management theories using ANTi-History to intergenerational stories on kindness and bouncing back. Compassion and kindness, care ethics, and the framing of kindness are also a part of the text. Unbiased compassion and work on the continuing and chronic occupational hazards of sexual harassment and discrimination is presented as well as benevolent sexism and performative kindness. Kindness and communication, Kindness and leadership and a case study of Kindness in the public service are also offerings in this first book on Kindness at Work. Kindness in Management and Organizational Studies is ideal for undergraduate and graduate students in business, leadership, and human resources. It offers illuminating new perspectives and insights to scholars that enables the analyses of leadership and management styles, organizational psychology, and HR practice and theory.